2017
DOI: 10.28955/alinterizbd.335835
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Honeybee Pollination on Productivity and Quality of Strawberry

Abstract: 90% of the food stuff all around the world is obtained from plants. 77 % of these plant needs pollination by bees. Therefore, in order to achieve sufficient pollination, bee colonies are needed in florescence period. When pollination and fertilization do not occur in many species of horticultural crops, abscission takes place without the fruit's being able to complete its devolopment. In conditions where fecundation is insufficent, the shape of the fruits is deformed and product quality is low even if the frui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 4 publications
1
8
0
2
Order By: Relevance
“…Managed bees alone were found to be effective in strawberry pollination. Colak et al (2017) found a significant difference in weight for honey bee pollinated strawberry. However, reliance on several pollinators would lead to better quality and quantity of strawberry fruits.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Managed bees alone were found to be effective in strawberry pollination. Colak et al (2017) found a significant difference in weight for honey bee pollinated strawberry. However, reliance on several pollinators would lead to better quality and quantity of strawberry fruits.…”
Section: Discussionmentioning
confidence: 92%
“…The quality and quantity of strawberry fruits was determined using the following fruit parameters: total number of seeds per berry, the equatorial diameter, polar diameter and the weight of the berry (Colak et al, 2017). Harvesting of the fruits was done after every seven days for a duration of three months.…”
Section: (2002)mentioning
confidence: 99%
“…Usually effective pollination has fortunate consequences on the post-harvested qualitative attributes like color, nutrient profile, size, firmness and overall shelf life of several fruits i.e. strawberry, feijoa, apples and almonds (Patterson, 1990;Brittain et al, 2014;Klatt et al, 2014a;Abrol et al, 2017b;Colak et al, 2017). These post-harvest qualities have strong link with the market value of fruits and economy of farmers (Klatt et al, 2014b).…”
Section: Discussionmentioning
confidence: 99%
“…Lebah piaraan yang perlu dikembangkan dan dimasyarakatkan kepada petani stroberi adalah lebah madu A. cerana dan teuweul T. laeviceps atau spesies lebah lainnya. Berbagai penelitian menunjukkan penyerbukan dengan A. mellifera dapat meningkatkan bobot dan kualitas buah stroberi yang dihasilkan (Free 1968;Nye & Anderson 1974;Goodman & Oldroyd 1988;Colak et al 2017). Partap (2000) melaporkan terjadi peningkatan bobot buah stroberi sebanyak 47,9% pada petakan stroberi yang dikurung bersama A. cerana dibandingkan dengan petak kontrol.…”
Section: Pembahasanunclassified